The Environmental Degradation on Human Health and Welfare - Umar, Risa Bernadip; B, Muslimin; A, Adhyatma; Rizki, Zuriani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Environmental degradation is a global issue that has a significant impact on human health and welfare. This research aims to analyze in depth various forms of environmental degradation that harm human physical, mental, and social well-being. This study uses secondary data analysis methods from various related research studies as well as an interdisciplinary approach to digging deeper into the relationship between damaged environments and disease prevalence, as well as deterioration in quality of life. Environmental degradation, which includes air pollution, habitat destruction, water pollution, and climate change, is one of the greatest challenges facing humanity today. Through a multidisciplinary approach combining data from epidemiological, ecological, and public health research, this study explores the relationship between declining environmental quality and the increasing prevalence of various diseases and their impact on quality of life. It was found that long-term exposure to harmful pollutants increases the risk of chronic diseases such as cardiovascular and respiratory diseases, while ecosystem damage significantly affects food security and nutrition. Furthermore, climate change is increasing the occurrence of extreme weather phenomena, which not only pose physical risks but also psychological stress. This article emphasizes the importance of effective policies and interventions to reduce environmental impacts on human health in promoting greater environmental sustainability for a healthier future.